Dampak Penggunaan Aplikasi Tiktok pada Perkembangan Kognitif Siswa Kelas V Sekolah Dasar - Apriliyah, Putri; Ningrum, Dwi Agus Tina; Setiyawan, Hery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the impact of using the TikTok application on the cognitive development of fifth-grade elementary school students. This research employs a descriptive qualitative approach with data collection techniques based on a literature review from various credible sources, such as scholarly journals and relevant articles. The data analysis technique used is content analysis of findings and results from the reviewed literature. The results indicate that TikTok usage has dual impacts. On the positive side, it enhances creativity, memory, curiosity, knowledge exploration abilities, and learning motivation. However, uncontrolled use can lead to decreased concentration, exposure to inappropriate content, and the emergence of negative behaviors. Therefore, guidance and supervision from parents and teachers are essential to ensure that TikTok usage provides optimal benefits for children's cognitive development.